2017
DOI: 10.1111/ctr.13117
|View full text |Cite
|
Sign up to set email alerts
|

Kidney allograft failure in the steroid‐free immunosuppression era: A matched case‐control study

Abstract: We studied the causes and predictors of death-censored kidney allograft failure among 1670 kidney recipients transplanted at our center in the corticosteroid-free maintenance immunosuppression era. As of January 1, 2012, we identified 137 recipients with allograft failure; 130 of them (cases) were matched 1-1 for recipient age, calendar year of transplant, and donor type with 130 recipients with functioning grafts (controls). Median time to allograft failure was 29 months (interquartile range: 18-51). Physicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…Increasing evidence has demonstrated that kidney transplantation can effectively improve the quality of life and survival rates of patients with chronic kidney disease and end-stage kidney disease [ 3 ]. However, the occurrence of allograft rejection following kidney transplantation greatly limits the success rate by resulting in degradation of kidney function and graft loss [ 4 , 5 ]. Although the current advancements in the development of immunosuppressive medications targeting T cell-mediated immunity have effectively inhibited the occurrence of rejection reaction [ 6 ], the currently available immunosuppressive medications are ineffective against the adaptive humoral immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has demonstrated that kidney transplantation can effectively improve the quality of life and survival rates of patients with chronic kidney disease and end-stage kidney disease [ 3 ]. However, the occurrence of allograft rejection following kidney transplantation greatly limits the success rate by resulting in degradation of kidney function and graft loss [ 4 , 5 ]. Although the current advancements in the development of immunosuppressive medications targeting T cell-mediated immunity have effectively inhibited the occurrence of rejection reaction [ 6 ], the currently available immunosuppressive medications are ineffective against the adaptive humoral immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Immunological injury to the allograft results from the interactions between the donor and recipient genomes. Acute allograft rejection (AR) is a major risk factor for long-term graft failure (5,6). While the clinical application of potent immunosuppressive and anti-infective prophylactic drugs is a major reason for the current success rates, there is continuing need for better understanding of the alloimmune response to further optimize patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Immune rejection of the allograft remains a signi cant challenge despite the use of potent immunosuppressive drugs [7][8][9] . Rejection episodes restrict the bene ts of transplantation and has a documented negative effect on long-term kidney allograft survival 10 .…”
Section: Introductionmentioning
confidence: 99%